The influence of the trainer`s social behaviors on the resilience, anxiety, stress, depression and eating habits of athletes - Trigueros, R.; Mercader, I.; González-Bernal, J. J.; Aguilar-Parra, J. M.; González-Santos, J.; Navarro-Gómez, N.; Soto-Cámara, R. (Nutrients, 2020)
During their sporting lives, athletes must face multiple di culties that can have consequences for their mental health and changes in their eating patterns. Therefore, the present study aims to analyze how social skills of the trainer influence the coping capacity, psychological well-being, and eating habits of the athlete, elements that are key to achieving success during competition. This study involved 1547 athletes and 127 trainer. In order to achieve the objective, the mean, standard deviation, bivariate correlations, reliability analysis and a structural equation model were analysed. The results showed that prosocial behaviours were positively related to resilience, while antisocial behaviours were negatively related. Resilience was negatively related to anxiety, stress and depression. Finally, anxiety, stress and depression were negatively related to healthy eating and positively related to unhealthy eating. These results highlight the importance of creating a positive social climate to develop coping strategies that promote mental health and healthy eating habits of athletes.